Chemokine Receptor Ccr6 Deficiency Alters Hepatic Inflammatory Cell Recruitment and Promotes Liver Inflammation and Fibrosis. - Silvia Affò; Daniel Rodrigo-Torres; Delia Blaya; Oriol Morales-Ibanez; Mar Coll; Cristina Millán; José Altamirano; Vicente Arroyo; Joan Caballería; Ramón Bataller; Pere Ginès; Pau Sancho-Bru (PLoS ONE, 2015)
Chronic liver diseases are characterized by a sustained inflammatory response in which chemokines and chemokine-receptors orchestrate inflammatory cell recruitment. In this study we investigated the role of the chemokine receptor CCR6 in acute and chronic liver injury. In the absence of liver injury Ccr6-/- mice presented a higher number of hepatic macrophages and increased expression of pro-inflammatory cytokines and M1 markers Tnf-α, Il6 and Mcp1. Inflammation and cell recruitment were increased after carbon tetrachloride-induced acute liver injury in Ccr6-/- mice. Moreover, chronic liver injury by carbon tetrachloride in Ccr6-/- mice was associated with enhanced inflammation and fibrosis, altered macrophage recruitment, enhanced CD4+ cells and a reduction in Th17 (CD4+IL17+) and mature dendritic (MHCII+CD11c+) cells recruitment. Clodronate depletion of macrophages in Ccr6-/- mice resulted in a reduction of hepatic pro-inflammatory and pro-fibrogenic markers in the absence and after liver injury. Finally, increased CCR6 hepatic expression in patients with alcoholic hepatitis was found to correlate with liver expression of CCL20 and severity of liver disease. In conclusion, CCR6 deficiency affects hepatic inflammatory cell recruitment resulting in the promotion of hepatic inflammation and fibrosis.